Assessment of Integrated Farming System of Beef Cattle in South Sulawesi - Matheus Sariubang; Andi Ella; A Nurhayu; Daniel Pasambe (Indonesian Center for Animal Research and Development, 2002)
Increase productivity of beef cattle can be done as integrated in the farming systems, where beef cattle has optimized the use of straw agricultural. Like rice straw, rice bran, stalk and corn bran, with legumes. In addition, beef cattle's feces could be used as compost to organic fertilizer for paddy and crops planted. The assessment was conducted in Takalar and Barru district with two farmer's group. In Takalar district of has implemented the collective stable, while that in Barru district was the individual stable. Result showed that aplication non limited rice straw + 3 kg refined rice bran + 10 g mineral (salt + manure SP 36) could increased body weight up to 0.41 kg/head/day in Barru district, and substitution in organic fertilizer (recommendation manure) with organic fertilizer on paddy has reached up to 6.50 ton/ha (1 ton organic manure + 127.8 kg urea + 100 kg ZA + 8.3 kg SP 36 + 41.7 KCl) and 6.37 ton/Ha (150 kg urea + 100 kg ZA + 50 kg SP 36 + 50 kg KCl). Key words: Farming system, beef cattle, organic fertilizer